Optimalisasi Model Layanan Hybrid IKD Sebagai Alternatif Kebijakan di Wilayah Sulit di Kabupaten Kampar - Yahya, MHD. Rafi; M Fajar Anugerah; Ilham Yuri Nanda (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to examine the optimization of the Digital Identity (IKD) hybrid service model as an alternative policy to accelerate the digital transformation of population administration services in the difficult areas of Kampar Regency. The method used is descriptive qualitative with data collection through in-depth interviews, observation, and documentation of relevant stakeholders. Purposive and snowball sampling techniques were used in selecting informants. The results of the study indicate that a hybrid service model that combines digital and manual services based on mobile services can be an adaptive solution to overcome the constraints of limited internet access, low digital literacy, and limited resources in the implementation of the IKD policy. However, the implementation of this model still faces challenges related to infrastructure readiness, budget support, and uneven community participation. This study emphasizes the importance of synergy between the central and regional governments, the empowerment of village officials, and digital literacy campaigns to improve service effectiveness. This hybrid model provides flexibility as an inclusive approach to ensuring access to valid population documents for the entire community, especially in remote areas.